Broad (multilevel) safety research and strategy. A sociological study. (April 2021) - Le Coze, Jean Christophe
Highlights: Safety is a product of how artefacts, people and institutions interact. Broad (or multilevel) safety research is a challenging empirical and theoretical endeavour. The literature emphasises the importance of powerful strategic decision makers in broad (multilevel) safety research. An ethnographic case study illustrates this approach with a narrative revealing complex patterns of interactions. Abstract: Studying safety from a broad (or multilevel) perspective in daily operations is a challenging prospect. The aim of this article, with the help of a case study, is to contribute to its development. In the introduction, broad (multilevel) safety research is introduced. This introduction indicates main authors who have produced in the past thirty to forty years a strong background against which one can build an idea of this challenge. It requires to decipher in real life situations the interactions between technology, task, structure, culture, strategy and environment of high-risk systems. An additional interest is, following the insights gained from the literature, to investigate the importance of strategic decision making in such broad (multilevel) safety approach. A first section discusses methodological issues linked to ethnographic research, and presents the methodology followed. The second section provides a narrative of the case study which combines a historical view of the plant, a description of some of the salient problems of working practices in a production department, an explanation of these problems through an organisational and managerial perspective, a description of the complex patterns of interactions between people in the plant and a strategic analysis of the situation. The last section discusses the interest of a broad (multilevel) research agenda explicitly incorporating the importance, influence and centrality of powerful decision makers, without simplifying the complexity of this issue.